2017
DOI: 10.1055/s-0036-1588671
|View full text |Cite
|
Sign up to set email alerts
|

A Decade Update on Benzoxazoles, a Privileged Scaffold in ­Synthetic Organic Chemistry

Abstract: In 2014, more than 80% of the marketed drugs in the US contained heterocyclic compounds, which play a major role in the drugdiscovery process, as one of the primary components. Benzoxazole, consisting of an oxazole ring fused with a benzene ring, has shown profound impact in drug discovery research owing to its important bioactivity. This moiety has also shown important properties in material science. The synthesis of this privileged scaffold from readily available chemicals remains a primary focus for the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 67 publications
1
27
0
1
Order By: Relevance
“…Các dẫn xuất của axit carboxylic cũng được sử dụng như acid chloride, nitrile, imidate, orthoester, anhydride, lactone... [4]. Mặt khác, aldehyde có thể được sử dụng cùng các chất oxy hóa khác nhau, chẳng hạn như nitrobenzene, benzoquinone, sodium metabisulfite, oxit thủy ngân, chì tetraacetate, iốt, đồng(II) acetate, và không khí được sử dụng cho mục đích này [4] xúc tác và chất oxy hoá đắt tiền, có cấu trúc phức tạp, đòi hỏi áp suất cao, nhiệt độ cao và dưới điều kiện chiếu xạ vi ba [5]. Mặt khác, tổng hợp các dẫn xuất của benzoxazole thường đi theo con đường truyền thống không trải qua quá trình oxi hóa khử (sơ đồ 1).…”
Section: Mở đầUunclassified
“…Các dẫn xuất của axit carboxylic cũng được sử dụng như acid chloride, nitrile, imidate, orthoester, anhydride, lactone... [4]. Mặt khác, aldehyde có thể được sử dụng cùng các chất oxy hóa khác nhau, chẳng hạn như nitrobenzene, benzoquinone, sodium metabisulfite, oxit thủy ngân, chì tetraacetate, iốt, đồng(II) acetate, và không khí được sử dụng cho mục đích này [4] xúc tác và chất oxy hoá đắt tiền, có cấu trúc phức tạp, đòi hỏi áp suất cao, nhiệt độ cao và dưới điều kiện chiếu xạ vi ba [5]. Mặt khác, tổng hợp các dẫn xuất của benzoxazole thường đi theo con đường truyền thống không trải qua quá trình oxi hóa khử (sơ đồ 1).…”
Section: Mở đầUunclassified
“…11-14 Its structure was then authenticated by 1 H-NMR, 13 C-NMR, FT-IR and TGA. An equimolar mixture of triphenylphosphine and 1,4-butane sultone in toluene solvent (10 mL) was stirred and heated at reux for 12 h to obtain the zwitterion as a white solid.…”
Section: Preparation Of Triphenyl(butyl-3-sulphonyl)phosphonium Toluementioning
confidence: 99%
“…The nal product was obtained aer solvent removal by a rotary evaporator followed by the purication on a silica gel column chromatography using acetone/petroleum ether (1/19) as an eluent solvent. The structural characterization was performed using 1 H, 13 C-NMR, and GC-MS. The recovered catalyst was reactivated by heating under reduced vacuum at 80 C for 30 min and reused for next cycles.…”
Section: Preparation Of Triphenyl(butyl-3-sulphonyl)phosphonium Toluementioning
confidence: 99%
See 1 more Smart Citation
“…Benzoxazoles represent an important class of chemical entities in medicinal chemistry as building blocks for modulating a ligand's affinity and/or selectivity towards a particular target and therefore benzoxazole scaffold is often found in ligands targeting a plethora of receptors and enzymes. Benzoxazole derivatives have been reported to show a wide range of biological activities such as antibacterial, antifungal, antiviral, anticancer, and antioxidant activities [4][5][6]. In particular, recent studies have indicated that benzoxazole derivatives show potent antitumor activity against different cancer cell lines [7][8][9][10][11][12] through the inhibition of Aurora B kinase [8], cyclooxygenase-2 (COX-2) [9,10], topoisomerase II [11] and the induction of Caspase-3 dependent apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%